Interview with Gilles Mercier (1963) by Luis Alvarado - Alvarado, Luis (2024)
Gilles Eric Mercier Tsuchiya is one of the most prolific Peruvian composers of electronic music, and at the same time one of the least studied. He has composed around 30 works, including mixed pieces and experimental works of an improvisatory nature and with live electronics. His first approaches to the use of electronic sounds date back to the early 80s. He has also made music for films and is the first musician of his generation to set up a personal laboratory for the production of electronic music at the beginning of the 90s. He is currently very active in the production of electroacoustic works.